2004
DOI: 10.1124/mol.104.006577
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Small Molecule Activator of the Human Ether-a-go-go-Related Gene (HERG) Cardiac K+ Channel

Abstract: Many drugs inhibit the human ether-a-go-go-related gene (HERG) cardiac Kϩ channel. This leads to action potential prolongation on the cellular level, a prolongation of the QT interval on the electrocardiogram, and sometimes cardiac arrhythmia. To date, no activators of this channel have been reported. Here, we describe the in vitro electrophysiological effects of (3R,4R)-4-[3-(6-methoxyquinolin-4-yl)-3-oxo-propyl]-1-[3-(2,3,5-trifluoro-phenyl)-prop-2-ynyl]-piperidine-3-carboxylic acid (RPR260243), a novel acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
189
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(194 citation statements)
references
References 22 publications
5
189
0
Order By: Relevance
“…HERG blockade is the major determinant of drug-induced QT prolongation and TdP. The first drug in this class, RPR260243, was shown to reverse dofetilide-induced APD prolongation in guinea pig myocytes (Kang et al, 2005). More potent than the first agent, PD-118057 was found to reduce the APD of endocardial and epicardial cells and abbreviate the QT interval when infused alone in rabbit left ventricular wedge (Zhou et al, 2005).…”
Section: Sodium Channel Blocker-lqt3mentioning
confidence: 99%
“…HERG blockade is the major determinant of drug-induced QT prolongation and TdP. The first drug in this class, RPR260243, was shown to reverse dofetilide-induced APD prolongation in guinea pig myocytes (Kang et al, 2005). More potent than the first agent, PD-118057 was found to reduce the APD of endocardial and epicardial cells and abbreviate the QT interval when infused alone in rabbit left ventricular wedge (Zhou et al, 2005).…”
Section: Sodium Channel Blocker-lqt3mentioning
confidence: 99%
“…Molecules activating hERG have also been found [172][173][174][175][176]. Furthermore, auxiliary subunits can also work as binding sites for some channel activators [177].…”
Section: Small-molecule K-channel Openersmentioning
confidence: 99%
“…RPR260243 dramatically slows current deactivation in patch-clamp experiments, and its effect is temperature and voltage dependent. Though it is a weak inhibitor of the L-type Ca 2+ channel, RPR260243 has no significant effects on the human cardiac Na + channel or the KCNQ1/KCNE1 cardiac K + channel, which are also linked with LQTS, thus showing high selectivity for hERG [22] . Interestingly, RPR260243 inhibits the erg3 channel, which is in the same family as hERG, and a single S5 residue may account for this difference in pharmacology (Thr556 in hERG, Ile558 in rERG3).…”
Section: Herg Activatorsmentioning
confidence: 99%
“…Additionally, RPR260243 enhances the delayed rectifier current in guinea pig myocytes and can, to some extent, reverse dofetilide-induced prolongation of action potential. Physiologically, it has been reported that RPR260243 can increase the T-wave amplitude, prolong the PR interval and shorten the QT interval in guinea pig hearts [22] .…”
Section: Herg Activatorsmentioning
confidence: 99%
See 1 more Smart Citation